The Main Clinical Signs, Symptoms, Treatment Methods of Liver Cancer - Rakhmatova Khilola Abdurashidovna (Genius Journals, 2022)
This article discusses the main clinical signs, symptoms and treatment of liver cancer. Primary liver cancer is the most dangerous type of cancer affecting the digestive organs. But in recent years, the treatment of this type of cancer has made no small progress.
Keywords: Liver Cancer; Symptoms; Healing; Treatment